Encapsulation of supported g‐C3N4/Au with metal–organic frameworks for enhanced stability towards photocatalytic hydrogen evolution. (1st September 2018) - Zhang, Zewu; Wang, Qikang; Wu, Qiong; Rao, Qingxu; Hang, Zusheng; Bu, Xiaohai; Shi, Haojun
Abstract : The supported graphitic‐carbon nitride (g‐C3 N4 )/Au composite has attracted considerable attention as an alternative visible‐light photocatalyst for hydrogen evolution reactions. However, the short‐term photocatalytic durability greatly limits their practical application. In this work, porous [Zn(BDC)(H2 O)2 ] n, which is a typical two‐dimensional metal–organic frameworks (MOFs), was used as the protecting material to encapsulate g‐C3 N4 /Au. The obtained g‐C3 N4 /Au@[Zn(BDC)(H2 O)2 ] n catalyst was composed of lamellar MOFs shells and g‐C3 N4 /Au cores. The catalysts exhibited an excellent catalytic activity and particularly superior stability as compared to the bare g‐C3 N4 /Au. The encapsulation method by using MOFs as the protective shell provides an alternative strategy for designing photocatalysts with high catalytic performance.